Pengaruh Kredit Bermasalah, Modal Sendiri dan Volume Usaha terhadap Sisa Hasil Usaha Koperasi Pegawai Negeri Guru Agama Batipuh - Sari, Chitra Indah (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2018)
The purpose of this research is as follows: 1) to find out how much problem loans affect SHU KPN-GA Batipuh 2) to know how big of own capital influence SHU KPN-GA Batipuh 3) to know how big business volume influence SHU KPN -GA Batipuh.This research takes place in the Cooperative Islamic Teacher in Batipuh District Tanah Datar. The data collected are quantitative data from RAT reports of civil Islamic teacher cooperative Batipuh in 2010-2015. Data analysis was done by multiple linear regression method. The result of data analysis is known that the problem loans, own capital and business volume simultaneously have significant effect to the Business Result Residual (SHU) of Cooperative Islamic Teacher Batipuh. The problem of non performing loans has the most dominant effect on the Business Result of Islamic Teacher Cooperative (KPN-GA) Batipuh.Based on the results of the research, it is suggested that there should be handling of non-performing loans, increase business capital and lower interest rates, as it will affect the remaining results of operations.